Peace, love and hope: a rural farm dwelling and labouring community's embodied knowledge of wellness and repair in an environment that continues to harm - Conradie, Une (Department of Philosophy, 2025)
Farm labouring and dwelling communities are considered among the most vulnerable populations in South Africa. The vast majority of health and wellness studies in these communities focus on the harmful social, psychological and biological impacts of historical, structural and institutional violence. What has not received sufficient attention is how farm labouring and dwelling communities resist the impacts of ongoing violence. This multimodal study engaged twenty-six participants living and working in a small rural farming community in the Cederberge in an arts-based research process to explore their embodied knowledge of wellness and repair in an environment that continues to harm. The arts-based research process was rooted in Victor Turners' adaptation of liminality to facilitate the co-creation of a research space where the research participants could be both the observers and the observed. What emerged from the participants' artworks, stories, and reflections was their insights and wisdom into wellness and repair, which mirrors contemporary discussions in Anthropology, Psychology, Neuroscience and the Applied Arts. The research participants portrayed wellness as inseparable from their relationships, emphasising their ability to communicate as a connected and loving community as the foundation for wellness. Embodied love also played a central role in how the research participants portrayed their capacity for daily repair in an environment that causes daily ruptures. By layering the research participants' art, stories and reflections with an interdisciplinary exploration of trauma, the study highlights the importance of being witnessed and bearing witness to moments of resistance and connection to build a collective capacity for repair in an environment that continues to harm.